A Possible Continental Free Trade Agreement in Africa for Trade Integration: The Perspectives Between Reality and Myth - (:unkn) unknown (My University, 2021)
With a view to intra-regional trade integration, African countries have decided to create an African Continental Free Trade Area (ACFTA) which should establish the rules and political guidelines necessary to promote intra-regional trade but the success of such political choice is conditioned by the degree of complementarity between the economies of these countries as well as their establishment in a win-win approach. In order to assess the prospects for the creation of the ACFTA and specifically on the Moroccan economy by integrating the specificities and potentials of African countries, the estimation of the potential has, however, shown the existence of a significant global potential for Morocco which can be exploited. To do this, the implementation of the ACFTA should allow the dismantling of tariff and non-tariff barriers under the condition of a great diversification of Moroccan products exported regionally which is necessary. The empirical study by integrating the gravitational model and economic variables for the period 2001-2019 on a sample of 50 African countries has made it possible to detect a potential to be exploited but the experience of failure of the already existing interregional communities presupposes a structural transformation of a commercial order, piloting by better diversity and integration of the production chain reinforced by good infrastructure and logistics, and of a political order by boycotting with historical factors and individualism for the benefit of a goal and a lucrative common identity for all countries.
Keywords: African Research